Protective Effect Of Opuntia Elatior And Withania Somnifera Against Lead Acetate Induced Toxicity In Broiler Chickens - Shah, T.M.; Nimavat, V.R.; Patel, U.D.; Bhadania, A.R.; Padodara, R.J.; Modi , C.M.; Patel, H.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was carried out to evaluate the protective effect of Opuntia elatior fruit juice (3 ml/kg body weight) and aqua-alcoholic extract of Withania somnifera (100 mg/kg body weight) alone and in combination of both against lead acetate (500 ppm in feed for 21 days) induced toxicity in broiler chickens (n=8 each) keeping one group each of lead induced toxicity and healthy control. Clinical symptoms of toxicity were observed in birds received only lead acetate. Haematological parameters, Hb and MCHC in birds treated with lead acetate were found significantly (P0.05) alterations in PCV, TEC, TLC and MCV levels of birds of all treatment groups were observed compared to that of control birds. Mean values of ALT, BUN, creatinine and total bilirubin were significantly (P
Keywords: Opuntia elatior; Withania somnifera; Lead acetate; Broiler chickens; Toxicity